2012
DOI: 10.1063/1.4759278
|View full text |Cite
|
Sign up to set email alerts
|

Ti-doped hematite nanostructures for solar water splitting with high efficiency

Abstract: Ti-doped hematite nanostructures have been synthesized for efficient solar water splitting by adding TiCN as the Ti precursor in a hydrothermal method. Ti-doped hematite nanostructures show an urchin-like morphology with nano feature size, which increases the effective surface area compared to undoped nanostructures. A remarkable plateau photocurrent density value of 3.76 mA/cm 2 has been observed for Ti-doped nanostructures under standard illumination conditions in 1 M NaOH electrolyte, which is 2.5 times hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
76
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 17 publications
8
76
2
Order By: Relevance
“…Figure S8D, Supporting Information shows the O 1s XPS spectra. The binding energies of O 1s for α‐Fe 2 O 3 (529.8 eV) and α‐Fe 2 O 3 /TiO 2 (530.4 eV) are similar to the values for α‐Fe 2 O 3 reported in literature . As determined by XPS analysis, surface atomic compositions of α‐Fe 2 O 3 /TiO 2 films are given in Figure S9A, Supporting Information.…”
Section: Resultssupporting
confidence: 82%
“…Figure S8D, Supporting Information shows the O 1s XPS spectra. The binding energies of O 1s for α‐Fe 2 O 3 (529.8 eV) and α‐Fe 2 O 3 /TiO 2 (530.4 eV) are similar to the values for α‐Fe 2 O 3 reported in literature . As determined by XPS analysis, surface atomic compositions of α‐Fe 2 O 3 /TiO 2 films are given in Figure S9A, Supporting Information.…”
Section: Resultssupporting
confidence: 82%
“…Ti-doping of hematite is a seductive idea to improve bare hematite properties and has been the subject of numerous studies in recent years [7,[10][11][12][13][14][15]. We have recently demonstrated that Ti-doping greatly enhances single crystalline hematite films water splitting performances by increasing both electrons and holes mobilities and also the free carrier concentration by one order of magnitude [10,11].…”
Section: Introductionmentioning
confidence: 98%
“…17,18 For instance, fabrication of nanostructured hematite (nanorods, nanowires, nanotubes…) 14,19,20 with the proper size has been proven to be an effective route to compensate diffusion length problem and to reduce the high recombination rate of photogenerated electrons and holes. 1,21 Different techniques have been examined to synthesize and control the morphology of hematite nanostructures such as spray pyrolysis, hydrothermal method, electrodeposition, and atmospheric pressure chemical vapor deposition (APCDV). 7,16,22,23 Incorporation or doping hematite with different metals such a Ti, 24,25 Si, 25 Cr, 26 Mn, 16 Sn, 18 Ni, 22 and Mg 27 have also been investigated and showed improved electrical and optical properties.…”
Section: Introductionmentioning
confidence: 99%